Growth trends for selected occupations considered at risk from automation. (Monthly Labor Review, 2022)
The article provides a list of occupations considered highly vulnerable to substitution by robots and artificial intelligence (AI) and examines the occupations' employment trends since 1999 and projected employment to 2029. Topics include the offsetting factors and other limitations of the automation, the impact of the computing capacities of new robots and AI on technological change and job displacement, and the projection models of the U.S. Bureau of Labor Statistics (BLS) on growth trends.